The Design of an Organic Chemistry Experiment focusing on Comprehensive Training in Common Laboratory Techniques - Tsz-Wing Wong (Recent Developments in Chemistry and Biochemistry Research Vol. 9, 2024)
In the sciences education, hands-on laboratory experiences are essential to the educational journey of students. These practical activities not only enrich the curriculum but also make learning more engaging and effective. By participating in laboratory experiments, students gain invaluable skills which can deepen their understanding of scientific concepts and enhance their overall science literacy. In organic chemistry, handling common laboratory techniques is crucial for successful experimentation. Skills such as reflux, simple distillation, liquid-liquid extraction and recrystallization are fundamental to the synthesis, isolation, purification and characterization of compounds. However, many traditional organic chemistry experiments are often designed with just one or two common techniques, which could hinder their comprehensive understanding of basic laboratory techniques. This article introduces an experiment designed to promote self-directed learning with pre-laboratory preparation, allowing students to engage with a broader range of techniques in organic synthesis. Aims: To design an experiment focused on student self-directed pre-laboratory preparation, utilizing a comprehensive approach that integrates various laboratory techniques in organic reactions. Study Design: A 2-hour laboratory session was designed that systematically organizes several common laboratory techniques, allowing students to practice these skills and perform product identification analysis. Place and Duration of Study: Department of Chemistry, Pui Ching Middles School, between 2021 and 2022. Methodology: 30 students work in groups of two. Benzophenone was reduced by NaBH4. The reaction mixture was heated under reflux for about five minutes. The product was then extracted by liquid-liquid extraction and simple distillation. The crude product was purified by recrystallization with hot hexane. Results: The percentage yield of diphenylmethanol is about 68%. Conclusion: The students experienced a series of laboratory skills through the organic experiment. Through hands-on chemistry experiments, students can investigate chemical properties and reactions by utilizing laboratory apparatus and instruments.